First Record of Pachnoda interrupta Olivier Outbreak on Sorghum, Pearl Millet and Sunflower in Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
During the autumn season of 2011, an outbreak of the sorghumchafer Pachnoda interrupta Olivier (Coleoptera: Cetoniidae) occurred forthe first time in Sudan on four genotypes of sorghum (Sorghum bicolor),four of pearl millet (Pennisetum glaucum) and eight of sunflower(Helianthus annuus) in the Gezira Research Station Farm. The objectiveof this study was to quantify the damage caused by the sorghum chafer tothese crops. The percentage of infested panicles (PIP), infested discs(PID), panicle damage (PPD) and disc damage (PDD) and number ofbeetles per panicle/disc were determined. Two sorghum genotypes(Jumbo and Pannar) showed tolerance to the beetle, as they scored thelowest PIP and PPD, whereas the other two (Kambal and Sugar graze)were highly susceptible. All pearl millet genotypes showed highsusceptibility, scoring a range of 92.9-94.2 PIP and 98.2-98.8 PPD.Alexandra sunflower genotype showed high tolerance, securing "zero"PID and PDD; Pac 361, Pan 7033, Pan 7351 and Hysun 33 genotypesshowed tolerance; Sirena and ARC 310 had comparatively high discattraction and grains sensitivity, and Pac 317 showed the highest discattraction and seed sensitivity to the beetle. The study concluded that P.interrupta has become a new potential serious pest of sorghum, pearlmillet and sunflower in Sudan. Infestation is variety/hybrid dependentwith sorghum and sunflower hybrids, and all tested pearl millet genotypeswere highly sensitive to the beetle.